Acute effects of a basketball match on urine protein/creatinine ratio in sub-elite women players in a sub-Saharan environment - TONON, Brigitte Affidéhomé; AGBOTON, LÉOPOLD BRUNO; GOUTHON, N. M. POLYCARPE; KOUSSIHOUEDE, Maddy; BIO NIGAN, ISSIAKO (My University, 2022)
Renal function is commonly evaluated by estimating glomerular filtration rate and proteinuria testing. A disturbance in the functioning of the kidneys may occur in top-level athletes during training and competition due to the associated high workloads and/or high water loss. This context requires the search for evaluation criteria more specific to athletes. In an effort to assess renal function during acute physical activity, this study evaluated the effects of a basketball match on urine protein/creatinine ratio (PCRurine) of women players in a sub-Saharan environment. An experimental study was conducted with 20 sub-elite female basketball players from the Republic of Benin. Urine proteins (UProt) and creatinine (UCrea), PCRurine and urine specific gravity (USG) were determined before, at the end and 24 hours after an experimental basketball match. Prior to the match, all players had normal values of each studied parameters, except for USG. UProt and UCrea increased by 64% (p = 0.0005) and 70% (p = 0.0006), respectively at the end of the match, but declined by 50% (p = 0.0001) and 51.5% (p = 0.0005), 24 hours later. The decrease in PCRurine during and 24 hours after the match was not significant (p ˃ 0.05). Under the study’s conditions, the basketball match induced transient proteinuria assessed by PCRurine in female sub-elite players. This non-invasive method could be used for frequent assessment of renal function in athletes with recourse to the invasive method if there was a strong suspicion of renal damage.
Keywords: Proteinuria; urine protein/creatinine ratio; basketball match; women players; Republic of Benin.